Gender Based Differences in Promotions of Clerical Workers - Swimmer, Gene (Relations industrielles / Industrial Relations)

(untitled) (Département des relations industrielles de l'Université Laval, 1990)
This paper aims at empirically addressing the issue of whether promotions of female clerical employees are less likely, when educational and other qualifications are held constant.